Withholding System PPh Pasal 23 Menggunakan Microsoft Visual Basic.Net - Suhartono, Suhartono; Hamid, Abdul; Santoso, Rame (Universitas Bina Sarana Informatika, 2018)
ABSTRACT - Sustainable national development from year to year to improve the lives and welfare of the people, requires the support of human resources, natural resources and huge financial resources. There are many financial resources that can be obtained by the state, one of them through taxes. Article 23 Income Tax as a source of state finance has problems in the process of cutting, depositing and reporting. An error occurring in the process may result in a deficiency in the amount of tax that should be deposited into the state treasury so as to prejudice and reduce state revenues. One method for managing tax payable taxpayers in order to enter the state treasury is to use the withholding system, in which the state authorizes third parties to deduct or levy the amount of tax payable by the taxpayer. There are many examples of cases that occur in tax evasion, where taxpayers pay little of their obligations to tax elements to enrich themselves and only a few are deposited into the state treasury. It takes good coordination and cooperation between related institutions and agencies so that leakage and tax evasion can be eliminated so that tax revenue can be increased. Keywords: Withholding, System, PPh, Article 23, Visual Basic.Net